Tridecanoin is anticonvulsant, antioxidant, and improves mitochondrial function. Issue 6 (June 2017) - Tan, Kah Ni; Carrasco-Pozo, Catalina; McDonald, Tanya S; Puchowicz, Michelle; Borges, Karin
The hypothesis that chronic feeding of the triglycerides of octanoate (trioctanoin) and decanoate (tridecanoin) in "a regular non-ketogenic diet" is anticonvulsant was tested and possible mechanisms of actions were subsequently investigated. Chronic feeding of 35E% of calories from tridecanoin, but not trioctanoin, was reproducibly anticonvulsant in two acute CD1 mouse seizure models. The levels of beta-hydroxybutyrate in plasma and brain were not significantly increased by either treatment relative to control diet. The respective decanoate and octanoate levels are 76 µM and 33 µM in plasma and 1.17 and 2.88 nmol/g in brain. Tridecanoin treatment did not alter the maximal activities of several glycolytic enzymes, suggesting that there is no reduction in glycolysis contributing to anticonvulsant effects. In cultured astrocytes, 200 µM of octanoic and decanoic acids increased basal respiration and ATP turnover, suggesting that both medium chain fatty acids are used as fuel. Only decanoic acid increased mitochondrial proton leak which may reduce oxidative stress. In mitochondria isolated from hippocampal formations, tridecanoin increased respiration linked to ATP synthesis, indicating that mitochondrial metabolic functions are improved. In addition, tridecanoin increased the plasma antioxidant capacity and hippocampal mRNA levels of heme oxygenase 1, and FoxO1 .